ANALISIS PREFERENSI KONSUMEN TERHADAP PRODUK SAYURAN ORGANIK (Studi Kasus Pelanggan Supermarket Total Buah Segar, Kecamatan Bekasi Utara, Kota Bekasi) - Fika Anggraini; Slamet Abadi; Suhaeni Suhaeni (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2023)
Public awareness of a healthy lifestyle has increased, especially in modern society, some people are becoming more selective in determining the vegetables to be consumed, even now some people are starting to set certain conditions in determining the vegetables to be purchased, one of which is organic vegetables. This study aims to determine consumer characteristics, the decision-making process in purchasing organic vegetables, and consumer preferences for the attributes of organic vegetables in the Total Buah Segar Supermarket, North Bekasi District. Using consumer preference theory and theory of planned behavior (TPB). In this study, researchers set 100 people as respondents with the accidental sampling method. The analytical method used is descriptive analysis and multiple linear regression. The independent variable is attitude, subjective norm, and behavioral control, as well as the dependent variable purchase intention. The buying decision-making process includes need recognition, information search, alternative evaluation, purchase decision and post-purchase evaluation. The results showed that subjective attitudes and norms had a significant effect on the purchase intention of organic vegetables. Behavioral control has no significant effect on the intention to buy organic vegetables in Total Buah Segar, North Bekasi District. The implications for Total Buah Segar, North Bekasi District, need to pay attention to consumer preferences in marketing strategies for organic vegetables and be more active in seeking information about consumer preferences on a regular basis, in order to be consistent in maintaining consumer satisfaction and always improving store facilities and the quality of organic vegetable products.